Japan's international relations politics, economics, and security - Hook, Glenn D.; Gilson, Julie; Hughes, Christopher W.; Dobson, Hugo (London Routledge, 2012)
This text examines the position of Japan in terms of its political, economic and security role in the three core regions of the global political economy, the United States, East Asia and Europe, as well as in the key global institutions.
"Simultaneouly published in the USA and Canada"--Title page verso.
Keywords: Japan -- Foreign relations -- 1989-.